Controlled Pauses at the Initiation of Sodium Nitroprusside Enhanced CPR Facilitate Neurological and Cardiac Recovery after 15 Minutes of Untreated Ventricular Fibrillation - Yannopoulos, Demetris (2012)
OBJECTIVE: A multi-pronged approach to improve vital organ perfusion during cardiopulmonary resuscitation (CPR) that includes sodium nitroprusside (SNP), active compression-decompression (ACD)-CPR, an impedance threshold device, and abdominal pressure (SNPeCPR) has been recently shown to increase coronary and cerebral perfusion pressures and higher rates of return of spontaneous circulation (ROSC) versus standard CPR. To further reduce reperfusion injury during SNPeCPR we investigated the addition of adenosine and four 20-second controlled pauses (CP) spread throughout the first 3 minutes of SNPeCPR. The primary study endpoint was 24-hour survival with favorable neurological function after 15 minutes of untreated ventricular fibrillation. (VF) DESIGN: Randomized, prospective blinded animal investigation. SETTING: Preclinical animal laboratory. SUBJECTS: 32 female pigs (4 groups of 8) 32±2Kg. INTERVENTIONS: After 15 minutes of untreated VF isoflurane anesthetized pigs received 5 minutes of either standard CPR, SNPeCPR, SNPeCPR+adenosine or CP-SNPeCPR+adenosine. After 4 minutes of CPR all animals received epinephrine (0.5 mg) and a defibrillation shock one minute later. SNPeCPR-treated animals received SNP (2 mg) after 1 minute of CPR and 1 mg after 3 minutes of CPR. After 1 minutes of SNPeCPR, adenosine (24 mg) was administered in two groups. MEASUREMENTS AND MAIN RESULTS: A veterinarian blinded to the treatment assigned a cerebral performance category score of 1–5 (normal, slightly disabled, severely disabled but conscious, vegetative state, dead, respectively) 24 hours after ROSC. SNPeCPR, SNPeCPR+adenosine, CP-SNPeCPR+adenosine resulted in significantly higher 24-hour survival rate compared to standard CPR (7/8, 8/8, 8/8 versus 2/8, respectively p<0.05). The mean CPC scores for standard CPR, SNPeCPR, SNPeCPR+adenosine or CP-SNPeCPR+adenosine were 4.6 ±0.7, 3±1.3, 2.5±0.9 and 1.5±0.9 (p<0.01 for CP-SNPeCPR+adenosine compared to all other groups). CONCLUSIONS: Reducing reperfusion injury and maximizing circulation during CPR significantly improved functional neurological recovery after 15 minutes of untreated VF. These results suggest that brain resuscitation after prolonged cardiac arrest is possible with novel non-invasive approaches focused on reversing the mechanisms of tissue injury.